Commentary: Constipation caused by anti-calcitonin gene-related peptide migraine therapeutics explained by antagonism of calcitonin gene-related peptide’s motor-stimulating and prosecretory function in the intestine - Mackenzie, Kimberly D.; Ortega, Mario; Kessler, Yoel; Campos, Verena Ramirez; Krasenbaum, Lynda J.; Carr, Karen; Ning, Xiaoping; Stratton, Jennifer (Frontiers in Physiology, 2022)
Calcitonin gene-related peptide (CGRP) pathway-targeted treatments have been shown to be efficacious in the prevention of episodic and chronic migraine. Currently approved therapies include monoclonal antibodies (mAbs) that target CGRP (eptinezumab, fremanezumab, and galcanezumab) and the CGRP receptor (erenumab), and small molecule CGRP receptor antagonists (atogepant and rimegepant). While CGRP pathway–targeted treatments are generally well-tolerated, in a review article by Holzer and Holzer-Petsche published in the January 2022 issue of Frontiers in Physiology the authors discussed the role of the CGRP pathway in gastrointestinal physiology, with a specific focus on constipation associated with the use of CGRP pathway–targeted treatments. The authors state that real-world surveys have shown constipation to be a “major adverse event” reported in “more than 50% of patients treated with erenumab, fremanezumab or galcanezumab.” As described in the current commentary, the limited data from the cited references in the review article by Holzer and Holzer-Petsche do not support that statement.